2018
DOI: 10.1080/10790268.2018.1521567
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of granulocyte-colony stimulating factor (G-CSF) treatment and exercise in rats with spinal cord injury

Abstract: Combined treatment provided more effective neuroplasty and functional recovery than individual treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Finally, the average data of the three trials was obtained. All animals were assessed 4 weeks after SCT 20,21 .…”
Section: Inclined Plane Testmentioning
confidence: 99%
“…Finally, the average data of the three trials was obtained. All animals were assessed 4 weeks after SCT 20,21 .…”
Section: Inclined Plane Testmentioning
confidence: 99%
“…In addition, NT3 further restored KCC2 expression by suppressing the hyper-excitatory state of the injured spinal cord [ 47 , 93 ] and induced an increased electrophysiological response and retrograde tracer transport [ 51 ]. When combined with rehabilitative training, GDNF and G-CSF induced neuroprotection [ 52 , 53 ], and a cocktail of neurotrophic factors induced neural regeneration when applied with cABC [ 54 ]. Because rehabilitative training, especially physical exercise, upregulates these neurotrophic factors regardless of chronicity [ 94 ], the treatment effect of trophic factor(s) will be enhanced when combined with training.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers reported negative results regarding gross tissue histology. A few studies reported tissue sparing, including suppression of cavity expansion or lesion extension, in combination with G-CSF and tamoxifen [ 52 , 83 ], and one study reported a positive trend with a growth factor cocktail [ 54 ], but studies on amphetamine, blood glucose scavenger, PKA inhibitor, and melatonin reported negative results [ 79 , 82 , 86 , 89 ]. Reporting bias might be involved because this assessment is fundamental.…”
Section: Discussionmentioning
confidence: 99%
“…After a brain injury, astrogliosis (or reactive astrocytosis) is a critical process for healing the injured brain area. In a spinal cord injury model of rats, concomitant G-CSF treatment and exercise therapy are effective for motor function recovery [ 22 ]. In the current animal model, GFAP immunostaining indexes of CA1, CA3, and Purkinje neurons in the brain irradiation-G-CSF group were lower than in the brain irradiation-saline group.…”
Section: Discussionmentioning
confidence: 99%